(untitled) (Journal of Engineering, 2020)
In past years, structural pavement solution has been combined with destructive testing; these destructive methods are being replaced by non-destructive testing methods (NDT). Because the destructive test causes damage due to coring conducted for testing and also the difficulty of adequately repairing the core position in the field. Ultrasonic pulse velocity was used to evaluate the strength and volumetric properties of asphalt concrete, of binder course. The impact of moisture damage and testing temperature on pulse velocity has also been studied. Data were analyzed and modeled. It was found that using non-destructive testing represented by pulse velocity could be useful to predict the quality of asphalt concrete, the good correlation between the pulse velocity and the volumetric and strength properties. The potential benefit of using the wave parameters is for condition assessment of asphalt concrete. The moisture damage exhibits a negative influence on pulse velocity by 13%, while the testing temperature shows an effect on the pulse velocity.